Father Abraham Lincoln's relentless struggle to end slavery - Striner, Richard, 1950- (Oxford University Press, 2006)
"Father Abraham challenges recent portraits of Lincoln as an essentially passive politician and reluctant abolitionist. Exhaustively researched and crisply argued, this superb book gives us a new appreciation of Lincoln as moral leader."--BOOK JACKET.